Anglina, Star of the Show - Holabird, Katherine (Puffun Books, 2004)
Angelina is so excited to perform at the Mouseland Dance Festival that she doesn't help her grandparents clean their boat, but she ruins her dance costume and wonders how she will be able to make the show with nothing to wear